Nonlinear coupling between cerebral blood flow, oxygen consumption, and ATP production in human visual cortex - Lin, Ai-Ling (National Academy of Sciences, 2010)
The purpose of this study was to investigate activation-induced hypermetabolism and hyperemia by using a multifrequency (4, 8, and 16 Hz) reversing-checkerboard visual stimulation paradigm. Specifically, we sought to (i) quantify the relative contributions of the oxidative and nonoxidative metabolic pathways in meeting the increased energy demands [i.e., ATP production (J(ATP))] of task-induced neuronal activation and (ii) determine whether task-induced cerebral blood flow (CBF) augmentation was driven by oxidative or nonoxidative metabolic pathways. Focal increases in CBF, cerebral metabolic rate of oxygen (CMRO(2); i.e., index of aerobic metabolism), and lactate production (J(Lac); i.e., index of anaerobic metabolism) were measured by using physiologically quantitative MRI and spectroscopy methods. Task-induced increases in J(ATP) were small (12.2–16.7%) at all stimulation frequencies and were generated by aerobic metabolism (approximately 98%), with %ΔJ(ATP) being linearly correlated with the percentage change in CMRO(2) (r = 1.00, P < 0.001). In contrast, task-induced increases in CBF were large (51.7–65.1%) and negatively correlated with the percentage change in CMRO(2) (r = −0.64, P = 0.024), but positively correlated with %ΔJ(Lac) (r = 0.91, P < 0.001). These results indicate that (i) the energy demand of task-induced brain activation is small (approximately 15%) relative to the hyperemic response (approximately 60%), (ii) this energy demand is met through oxidative metabolism, and (iii) the CBF response is mediated by factors other than oxygen demand.